1998
DOI: 10.1076/opge.19.4.175.2310
|View full text |Cite
|
Sign up to set email alerts
|

Is pseudoexfoliation syndrome inherited? A review of genetic and nongenetic factors and a new observation

Abstract: Pseudoexfoliation (PEX) syndrome is the commonest identifiable cause of open-angle glaucoma worldwide. PEX is characterized clinically by small whitish deposits of fibrillar-granular material in the anterior segment of the eye. Despite its prevalence and potential for ophthalmic morbidity, surprisingly little is known about the etiology and pathogenesis of PEX. This article reviews the literature and presents evidence regarding genetic and nongenetic arguments for the etiology of pseudoexfoliation. Lines of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 34 publications
1
47
0
7
Order By: Relevance
“…28,29 Cumurcu et al 30 displayed that serum a 1-antitrypsin, an acute phase protein associated with inflammatory processes, was significantly higher in PEX patients than in controls. Fiore et al 31 found that eyes with PEX had a greater post-laser inflammatory reaction than eyes without PEX.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Cumurcu et al 30 displayed that serum a 1-antitrypsin, an acute phase protein associated with inflammatory processes, was significantly higher in PEX patients than in controls. Fiore et al 31 found that eyes with PEX had a greater post-laser inflammatory reaction than eyes without PEX.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the observation of two homozygote pairs of twins, one concordant and one discordant for the presence of PE syndrome, this was taken to indicate an environmental influence on the distribution of the PE syndrome (Ringvold et al 1988). However, as indicated recently by Damji et al (1998), it is possible that a combination of genetic and nongenetic factors may be involved in the etiology and pathogenesis of the PE syndrome, i.e. it may be a multifactorial disorder.…”
mentioning
confidence: 99%
“…2 The etiology of PEX syndrome is still poorly understood but increased prevalence of the disease in certain populations and observed familial aggregation are compatible with PEX being a complex genetic disorder. [3][4] Proteomic approaches identified the presence of elastic fiber components (such as fibrillin-1, vitronectin and fibulin-2), clusterin as well as apolipoprotein E (APOE) within PEX material deposits, suggesting them as possible functional candidate genes for PEX disease. [5][6] To date however, among these candidates only polymorphisms in the gene encoding for clusterin (CLU) have been shown to be associated both with PEX syndrome and PEX glaucoma (PEXG) in different populations.…”
Section: Introductionmentioning
confidence: 99%